PERILAKU KOMUNIKASI TOURGUIDE FREELANCE DALAM MEMPERKENALKAN OBJEK WISATA KOTA BUKITTINGGI - Wahyuni "; Tantri Puspita Yazid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Foreign tourists who come to the Country or any other city in need of a tour guide as a compass in a traveling tour. The existence of a very large tour guide in the introduction of a regional attraction like Bukittinggi. Given the differences in languages and cultural backgrounds differ, a tour guide must pay attention to how to communicate with foreign tourists so that effective communication. This study aims to determine the behavior of verbal communication and non-verbal communication freelance guide in introducing the attractions of Bukittinggi.This study uses a qualitative research approach symbolic interaction. Informants in this study were as many as seven people consisting of four freelance guide and three tourists who visit the city of Bukittinggi selected by using purposive. The collection of data obtained through observation, interviews and documentation. Technical analysis of the data in this study using interactive data model with data validity checking is done using the extension of participation and triangulation techniques.The results of this study indicate that the behavior of verbal communication with foreign tourists freelance guide includes vocabulary words using American English which will make communication more effective. Speed of communication that will influence on receipt of the message can be understood whether or vice versa. The emphasis or tone of voice used in explanations related to regional languages. While the humor is not boring interlude in communication, as well as a clear concise language used for communication is not wordy and attention to the time in conversation. As for the non-verbal communication behaviors freelance guide shows non-verbal communication kinesics which include facial expressions and eye contact when the communication process takes place. Furthermore, the message artifactual or appearance can give your sense of how to go about it and how he should communicate with foreign tourists in accordance with her appearance.Key word : Communication behaviour, verbal communication, non verbal communication